Study of diversity and morphometry in edible bivalves and gastropods from a coastal wetland in Sarawak - Idris, Mohd Hanafi; Hamli, Hadi; Mustafa Kamal, Abu Hena; Ab Lah, Roslizawati; Nik Jaafar, Nik Mohd Shibli (Prince of Songkla University, 2021)
Diversity and morphometry of edible, bivalve and gastropod classes of molluscs were investigated from July 2010 to January 2012, for a particular set of bivalve species, at selected coastal divisions of Sarawak including Kuching, Sibu, Mukah, Bintulu, Miri, Limbang, and Lawas. A total of 41 edible species were recorded and identified from 11 families of gastropods represented by 21 species, and from 12 families of bivalves represented by 20 species. For bivalves, species of the family Cyrenidae (Geloina erosa, G. expansa and G. bengalensis) were the most widely distributed bivalve species. The gastropod family Potamididae (Cerithidea obtusa, C. quadrata, C. rizophorarum and Telescopium telescopium) was also commonly observed over the entire seven divisions. Species diversity was found to be highest in Bintulu division for both classes, having 13 species of gastropods and 11 species of bivalves. Jaccard’s index showed high similarity amongst the edible bivalves for Limbang division with Miri division (0.75), and for Limbang with Lawas (0.75). For gastropods, Sibu versus Mukah showed high similarity (0.50). Morphometric study of the bivalves indicated that VPM/SL and LCT/SL features were applicable as an identification key to differentiate between Geloina spp. This morphometric identification key could be developed further for identification of other species in the mollusc family.